Óxido de Carmen by Ana María Del Río: a Feminicidal Suicide (Anclajes, 2020)
This article proposes reading Ana María Del Río’s novel, Óxido de Carmen (1986), from the concept of feminicidal suicide, coined by Diana Russell. This notion, common to contemporary gender theory, allows us to glimpse in this story, the repressive system in which the same family women act as agents of patriarchy. Carmen, the protagonist, will be house victim of gender violence on diverse grounds: spatially, she will be excluded from the main house; psychologically, she will experience the introjection of the Catholic religion and the idea of sin; and bodily, she will suffer from anorexia. These processes will conduct her into the female stereotype of passivity, domesticity and obedience to end up committing suicide. The rereading of this novel favors making visible the different types of violence that hang over women on a daily basis.
Keywords: Ana María Del Río; Chilean Literature; Gender Theory; Twentieth Century; Chile